PENGARUH LAMINAT SERAT RAMI DAN KARBON TERHADAP SIFAT MEKANIK KOMPOSIT HYBRID MATRIKS TUNGGAL EPOXY - Adityo Noor Setyo H.D; M. Fendy Kussuma H.S; Cahyo Sasmito (POLITALA PRESS, 2025)
. Composite materials have developed rapidly over the years and now play an important role in the advancement of materials technology. It is believed that the use of mixed (hybrid) composites between natural fibers and artificial (synthetic) fibers can produce better composites. This research aims to determine the effect of the arrangement of hybrid composite laminates reinforced with hemp fiber and carbon fiber using an epoxy resin matrix on mechanical properties, namely tensile strength and impact toughness. The composite was made using the hand lay up method with variations in the laminate composition, namely Carbon-Hemp-Carbon-Hemp and Hemp-Carbon-Carbon-Hemp. The hemp fiber was treated with alkali by soaking in 5% Naoh for 2 hours. The research results show that of the two specimen variations, the Hemp-Carbon-Carbon-Hemp variation has the highest tensile strength value of 245 MPa with the highest strain reaching 0.074 while the highest elastic modulus in the Carbon-Hemp-Carbon-Hemp variation is 6.04 GPa. Charpy impact testing obtained the highest impact value in the Hemp-Carbon-Carbon-Hemp variation of 0.07762 J/mm².